The used of aqueous urea solution in reduction of noxious emissions in bio fuel combustion system using selective non-catalytic reduction - Mohd. Jaafar, Mohammad Nazri (Canadian Center of Science and Education, 2011)
Selective Non-Catalytic Reduction (SNCR) of nitric oxide was studied experimentally by injecting different concentrations of aqueous urea solution; urea and ammonia in a pilot-scale Bio-fuel fired tunnel furnace at 3-4 % excess oxygen level and with low ppm of baseline NOx ranged from 65 to 75 ppm within the investigated temperature range. The furnace simulated small-scale combustion systems where the operating temperatures are usually in the range of about 973 to 1323 K and NOx emission level remains below 100 ppm. NOx reductions were studied with the variation of different parameters such as injection temperature, residence time, Normalized Stoichiometric Ratio (NSR) of the reagent, carrier gas pressure, etc. A significant result shows that for NSR, at higher NSR, ammonia could give significant reduction of NOx at the investigated injection temperature. Meanwhile, for the effect of residence time, both aqueous solution shows that the NOx reduction increased with increase in residence time. Finally for the effect on injection temperature, both aqueous solution, up to a certain temperature NOx reduction continued to increase with increasing injection temperature and afterward the reduction decayed with further increase in temperature.